The Effect of Drill Learning Method on Students’ Learning Outcomes in Multiplication Topic for Grade III Students at St. Yoseph 3 Catholic Elementary School - Kehi, Ayu Stefania S.; Nitte, Yulsy Marselina; Mbuik, Heryon Bernard (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The drill method is a learning approach that emphasizes continuous practice to build habits, improve accuracy, and develop specific skills. Conventional teaching methods often contribute to low student learning outcomes in mathematics, particularly in multiplication topics. Preliminary data from St. Yoseph 3 Catholic Elementary School showed that out of 32 third-grade students, 12 students (37.5%) achieved the minimum mastery criterion (75), while 20 students (62.5%) had not yet achieved it. This study aimed to determine the effect of the drill learning method on the learning outcomes of third-grade students at St. Yoseph 3 Catholic Elementary School. The study used a quantitative approach with a quasi-experimental design and a pretest-posttest control group design. A saturated sampling technique was applied involving 32 respondents. Data were collected through observation, tests, and documentation. The data analysis techniques included normality test, homogeneity test, and hypothesis testing using an independent t-test. The results showed that the average posttest score of the experimental and control classes was 85.31 > 75.00 with a difference of 10.31, while the average pretest score was 50.00 < 50.94. It can be concluded that students taught using the drill method achieved higher learning outcomes compared to those who were not, particularly in multiplication material.